2014
DOI: 10.14260/jemds/2014/3694
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Relative Correlation Between the Pattern of Finger Prints and Lip Prints

Abstract: BACKGROUND AND OBJECTIVE: The use of conventional methods such as dactylography (study of finger prints) & cheiloscopy (study of lip prints) is of paramount importance, since personal identification by other means such as DNA analysis is sophisticated and not available in rural and developing countries. Fingerprint in its narrow sense is an impression left by the friction ridges of human fingers. The second prints of interest are lip prints. Studies of association between finger print and lip prints are scanty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
(5 reference statements)
1
1
0
Order By: Relevance
“…If more than one pattern predominates it is taken as undetermined (type 5). In the present study type 2 is found to be dominant in females which is in accordance with a similar study done by Neha bansal, et al in a study sample of 2500 females and 2500 males stated that Type I, I', II lip print pattern was most predominant in females [32]. It is found in the study that lip prints are unique to each individual and a similar study done by Amrita, et al in a study sample of 200 medical students also stated the same [33].…”
Section: Discussionsupporting
confidence: 93%
“…If more than one pattern predominates it is taken as undetermined (type 5). In the present study type 2 is found to be dominant in females which is in accordance with a similar study done by Neha bansal, et al in a study sample of 2500 females and 2500 males stated that Type I, I', II lip print pattern was most predominant in females [32]. It is found in the study that lip prints are unique to each individual and a similar study done by Amrita, et al in a study sample of 200 medical students also stated the same [33].…”
Section: Discussionsupporting
confidence: 93%
“…Blood group, students obtained ABO process and each students bio data, cleiloscopy and dactylographic pattern were recorded, apply lipstick and glued portion of the cellophane tape was used to obtain the impression of the lip, immediately transferred onto paper by gently sticking the cellophane tape and analysis, each cheiloscopy was divided into six types, cheiloscopy classificated according to Suzuki and Tsuchihashi 13 , Type -I Clear cut grooves running vertically across the lip, Type -I' The grooves are straight but they disappear half way, Type -II The grooves fork in their way(branched), Type -III The grooves intersect, intersecting, Type -IV The grooves are reticular, reticular, Type -V The grooves do not fall in any of the types from I to IV, undetermined. Dactylographic pattern, imprint of both hands fingers was taken, pattern was examined by using magnifying glass, dactylographic pattern were classified according to Michael's and Kucken's 14 . Loop, Whorl, Arch, Composite containing two or more forms.…”
Section: Methodsmentioning
confidence: 99%